PENGUATAN PERLINDUNGAN HAK MEREK USAHA MIKRO DAN KECIL MAINAN PAPAN JARI “BLUE BOARD” MELALUI EDUKASI DAN PENDAMPINGAN PENDAFTARAN MEREK JAKARTA SELATAN - Afif, Muhammad; Amelia, Ravikah; Hadi, Rival Mahesa Fauzan; Ajrina, Denanda Zahra; Sirait, Zefania Augustine; Situngkir, Brian Bona T.; Fajar, Muhammad Rizky; Situmorang, Leonard Roderick; Farabi, Ahmad Abdillah; P, Calvin Philip Andrew; Fairuz, Muhammad; Putri, Aisyah Nikita Permata; Romadoni, Rahayu Mulia (Jurnal Kreatif : Karya Pengabdian untuk Masyarakat Aktif dan Inovatif, 2025)
Keywords: Abstract Intellectual Property Rights; Trademark Protection; Small and Micro Enterprises (SMEs)Finger Board; Intellectual Property Rights, particularly trademark rights, play an essential role for the Small and Micro Enterprise (SME) of “Mainan Papan Jari” located in Block A, Kebayoran Baru, Jakarta Selatan, which still faces the problem of limited understanding regarding the urgency of trademark protection and its registration procedures. The partner location was selected because the area serves as a center for creative SMEs that require enhanced legal literacy to strengthen their business identity. The implementation method involved legal counseling on the function and protection of trademarks, interactive discussions, and technical assistance in completing and submitting trademark registration documents to the Directorate General of Intellectual Property (DGIP). The results show that the partner experienced improved understanding of the legal and strategic benefits of trademark protection for business sustainability. Moreover, the provided assistance enabled the partner to complete the trademark registration process officially. This activity contributes to strengthening the legal protection of the business identity and enhancing the competitive value of the “Mainan Papan Jari” SME in an increasingly competitive market.